Knowledge, Attitudes, and Practices of Students Towards COVID-19 Guidelines in Bushbuckridge Local Municipality, Mpumalanga Province - Riborn Sibuyi; Bumani Solomon Manganye; Gudani Goodman Mukoma (COVID)
The level of knowledge, positive attitudes, and adherence to preventive practices among students towards COVID-19 guidelines is essential in minimising transmission and ensuring the maintenance of safe and healthy learning environments. The present study aimed to investigate students’ knowledge, attitudes, and practices towards COVID-19 guidelines at Bushbuckridge Local Municipality, Mpumalanga Province. A quantitative, cross-sectional, descriptive design was employed. Two-stage cluster sampling and systematic sampling were used to select respondents from each sampled school cluster. A total sample size of n = 364 was determined using the Raosoft sample size calculator, with a margin of error (e) of 5% and a confidence level of 95%. Out of the total, 357 respondents who returned the assent forms participated in the study. Data was collected through a questionnaire administered to selected respondents. The findings indicated that the majority of secondary school students possess a good level of knowledge regarding COVID-19 guidelines. Furthermore, 78% of these students have positive attitudes toward COVID-19 guidelines, and 72% exhibit proactive practices in adhering to these guidelines. The Department of Basic Education should emphasise the integration of health education in schools to enhance students’ understanding of COVID-19 guidelines and the virus itself. Continuous education on hygiene practices and COVID-19 guidelines is essential to ensure that students are prepared and able to comply during future pandemics.